Anticoagulation and outcomes after surgical aortic valve replacement with a biological prosthesis. (25th November 2020) - Angleitner, P; Zinggl, M; Werner, P; Coti, I; Mach, M; Kocher, A; Laufer, G; Andreas, M
Abstract: Background: No strong recommendation exists regarding the use of short-term anticoagulation after surgical aortic valve replacement (SAVR) with a biological prosthesis. Purpose: Our aim was to analyze outcomes of patients receiving warfarin versus low-molecular weight heparin (LMWH) after isolated SAVR. Methods: We retrospectively analyzed all adult patients who underwent surgery between 2009 and 2017 at our department (n=598). Exclusion criteria included pre-operative anticoagulation, atrial fibrillation, dialysis, previous aortic valve replacement, or active endocarditis. Patients who were discharged alive were stratified according to the type of anticoagulation (warfarin, n=332, 55.5%; LMWH, n=266, 44.5%). Long-term survival during the follow-up period was analyzed (median follow-up, 5.6 years). Results: Patients who received warfarin had significantly lower logistic EuroSCORE and were younger (Table 1). Warfarin was more frequently utilized between 2009 and 2014, whereas LMWH was more commonly used between 2015 and 2017. Kaplan-Meier curves in Figure 1 show that patients who received warfarin had significantly superior long-term survival (log-rank test: p=0.002). Multivariable Cox proportional hazards regression analysis confirmed that the use of warfarin was associated with significantly lower risk of long-term mortality when compared with LMWH (hazard ratio [HR] 0.50, 95% confidence interval [CI] 0.34–0.74, p=0.001). Covariables in this model included logistic EuroSCORE, era, and duration of cardiopulmonary bypass. Conclusions: The present analysis suggests that the use of warfarin is associated with significantly superior survival after SAVR with a biological prosthesis. Our findings require validation in a prospective randomized controlled trial. Funding Acknowledgement: Type of funding source: None